2017
DOI: 10.1155/2017/9053238
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Community Detection for DMA Creation: Criteria Analysis through Multilevel Optimization

Abstract: Management of large water distribution systems can be improved by dividing their networks into so-called district metered areas (DMAs). However, such divisions must be based on appropriated technical criteria. Considering the importance of deeply understanding the relationship between DMA creation and these criteria, this work proposes a performance analysis of DMA generation that takes into account such indicators as resilience index, demand similarity, pressure uniformity, water age (and thus water quality),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 38 publications
0
31
0
1
Order By: Relevance
“…They are usually related to economic feasibility [40][41][42] or the preservation of the hydraulic reliability of the WDN [11,17]; other aspects such as pressure uniformity and water quality issues are also included. In contrast to Ferrari et al [21] and Brentan et al [43], we try not to make the original flow velocity deteriorate, especially for pipes that originally had a low flow velocity. More attention can be paid to better execute pressure management [44] or more quickly detect and control accidental events (e.g., pipe bursts and water contamination) in future research.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually related to economic feasibility [40][41][42] or the preservation of the hydraulic reliability of the WDN [11,17]; other aspects such as pressure uniformity and water quality issues are also included. In contrast to Ferrari et al [21] and Brentan et al [43], we try not to make the original flow velocity deteriorate, especially for pipes that originally had a low flow velocity. More attention can be paid to better execute pressure management [44] or more quickly detect and control accidental events (e.g., pipe bursts and water contamination) in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, prior expert knowledge can be introduced in the form of rules (Gibert et al, 2010b) or ontologies (Gibert et al, 2014) to introduce semantic information into the process, and get classes easier to interpret. Graph theory (Herrera et al, 2015;di Nardo et al, 2018) and social network theory (Campbell et al, 2016;Brentan et al, 2017aBrentan et al, , 2018a have also found applications in clustering. Density-based methods, like DBScan (Ester et al, 1996) or OPTICS (Ankerst et al, 1999) are computation-based methods detecting areas with higher concentration of objects and work well with non-globular clusters.…”
Section: Profiling Dm Methods: Clustering and Density Estimationmentioning
confidence: 99%
“…A hybrid combination SOM+k-Means Clustering was used to improve planning, operation and management of Water Distribution Systems in Brentan et al (2018b), which can be easily extended to other environmental problems, etc. Graph theory (Herrera et al, 2015;di Nardo et al, 2018) and social network theory (Campbell et al, 2016;Brentan et al, 2017aBrentan et al, ,2018a have been used to cluster a water distribution network into sectors so as to optimize these infrastructures' management. In Blanco et al (2018) SCADA data is used to identify health profiles of wind turbines.…”
Section: Applications and Referencesmentioning
confidence: 99%
“…In this situation, a clever solution is to give each geodesic equal weight such that the weights add to unity [12,[26][27][28]. Newman [4] put forward another method assuming that the route of information spreading through is some kind of random walk.…”
Section: Optimal Route Between Nonadjacentmentioning
confidence: 99%